A nine-switch nine-level converter new topology with optimal modulation control - Radouane Majdoul; Abelwahed Touati; Abderrahmane Ouchatti; Abderrahim Taouni; Elhassane Abdelmounim (Institute of Advanced Engineering and Science, 2021)
Multilevel power converters are becoming increasingly used in several sectors: energy, grid-tie renewable energy systems, High voltage direct current (HVDC) power transmission, and a multitude of industrial applications. However, the multilevel converters consist of several drives and a high number of power switches, which leads to a considerable cost and an increased size of the device. Thus, a novel topology of a multilevel bidirectional inverter using a reduced number of semiconductor power components is proposed in this paper. Without any diode clamped or flying capacitor, only nine switches are used to generate nine voltage levels in this new topology. The proposed multilevel converter is compared with the conventional structures in terms of cost, the number of active power switches, clamped diodes, flying capacitors, DC floating capacitors, and the number of DC voltage sources. This comparative analysis shows that the proposed topology is suitable for many applications. For optimum control of this multilevel voltage inverter and to reduce switching losses in power semiconductors, a hybrid modulation technique based on fundamental frequency modulation and multi-carrier-based sinusoidal pulse-width modulation schemes is performed. The effectiveness of the proposed multilevel power converter is verified by simulation results.